Kemampuan Membaca Al-Qur’an Santri Rumah Tahfiz Sitiung Dharmasraya Dipengaruhi oleh Tehnik Tahsin - Renata , Reynaldo; Aprison , Wedra (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
The basic capacity of students in reading the Al-Qur'an which is the subject of this research at the Sitiung Dharmasraya Tahfiz school has not achieved optimal results and according to sources obtained during the learning process there are still students who read the Al-Quran only less commonly, hesitate when pronouncing the letters of the Al-Quran, it is impossible to differentiate the pronunciation of letters which are similar to the letters ù and ù and other letters, as well as a lack of understanding of Law and Tajweed when reading verses in the Al-Quran with this approach. using a quantitative approach. The research methodology used in this research is a quasi-experimental approach using a single subject group design. (single-group pre-posttest). The aim of this research is to determine the significant impact of the Tahsin method on the Maharjur script pronunciation abilities of Rumah Tafiz Sitiun Dharmasraya students. The subjects of this research were the students of Rumah Tafiz Sitiun Dharmasraya. The topic of this research is students' involvement in Tahsin learning and their ability to read the Al-Quran. Research findings show an average gap of -11. 50,000 between before and after the test. The sig (two-sided) value is 000 <. 0.05. The results of the pre-test and post-test show that there are significant differences in tahsin learning outcomes so that it can be concluded. Thus, it can be seen that the different approaches to tahsin taught influence how well students read the Al-Quran.